Potret Buram Keberagamaan Di Indonesia - Annur, Barsihannor (Jurnal Adabiyah, 2015)
Religious awareness is one of core values that human being has to posses. It is because, through this awareness, human being can build the mutual understanding between the adherents of religion. In fact, many adherents cannot live together and in harmony. They get conflict due to religion they believed. They are very intolerant to see the diversity. It seems to something ignored or destroyed. This writing discloses some facts how religion potentially become conflict if it is not well understood or organized. Besides, this article also gives some solution how to overcome the conflict.